Análisis a partir de la simulación de procesos productivos para la empresa Prefabricados del Sol S.A.S con énfasis a la reducción de costos - Osorio Niño, Jhon Sebastián; Vargas Gómez, Oscar Leonardo (Universidad Antonio Nariño, 2021)
The research is based on the simulation of production processes with emphasis on cost reduction for the company Prefabricados Del Sol located in the city of Sogamoso. The organization manufactures products from steel and cement, mainly for the electrical and construction sectors. The primary objective is the development of products by analyzing and simulating the production processes of the organization. The methodology presents the solution to be used and success stories that support the proposed proposal. For this reason, a model based on engineering will be used to determine the current production scenario in the organization and the possible causes that are generating the problem. All this information is compiled with the collaboration of the administrative and operational staff of the organization. Then, the proposals for solutions to the problems are raised and developed by means of the simulation analysis of the process and proposal for improvement in the processes by reducing costs, highlighting the economic benefit obtained through the application of the improvement. Keywords: Simulation, cost reduction, plant layout, productive improvem